Ensuring the Legality and Reasonability of Criminal Liability of a Person (Texas Journal of Multidisciplinary Studies, 2022)
The article discusses the scientific and theoretical issues of the protection of the rights and interests of the participants in the prosecution process. At the stage of initiating criminal proceedings, the tasks of ensuring the principles of legality and validity of prosecution will be considered.